Pendampingan Pembuatan Herbal Mineral Blok sebagai Suplemen Tambahan Ternak Ruminansia di Desa Tawangrejo - Widyaningrum, Dyah Puspa; Natasya, Dhea; Raihan, Raka; Quddusy, Fairuz Nabil; Rosalia, Annisa Wyne; Arum, Dewi; Hafizhoh, Putri Hasna; Syahidah, Hilyah; Listiyowati, Sri (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The village of Tawangrejo possesses several potential developments, particularly in the livestock sector, but the maintenance of livestock generally relies on forage without additional mineral supplements. Therefore, assistance is necessary to facilitate the production of Herbal Mineral Block (HMB) supplements for the breeders. This program is designed to impart knowledge and skills on producing additional mineral supplements for ruminant livestock feed to enable breeders to produce HMB supplements independently. The methods used were socialization, distribution of HMB informational leaflets, hands-on demonstrations of HMB production, and pre-test and post-test evaluations to measure the program's success. The results of the assessment of changes in conditions before and after the program showed that there was an increase in the knowledge, attitudes, and breeders’ skills of Tawangrejo. In the high category, the knowledge aspect increased from 14.3% to 100%, the attitude aspect increased from 57.1% to 100%, and the skills aspect increased from 4.8% to 95.2%. Through this program, Tawangrejo breeders are assessed as having an understanding of additional mineral supplements as important for livestock health and having the skills to make HMB independently. Adding HMB supplements to livestock can increase productivity, nutrient absorption, and body weight.